2016
DOI: 10.1002/hep.28900
|View full text |Cite
|
Sign up to set email alerts
|

A Karnofsky performance status–based score predicts death after hospital discharge in patients with cirrhosis

Abstract: Identification of patients with cirrhosis at risk for death within 3 months of discharge from the hospital is essential to individualize postdischarge plans. The objective of the study was to identify an easy-to-use prognostic model based on the Karnofsky Performance Status (KPS). The North American Consortium for the Study of End-Stage Liver Disease consists of 16 tertiary-care hepatology centers that prospectively enroll nonelectively admitted cirrhosis patients. Patients enrolled had KPS assessed 1 week pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 46 publications
0
70
0
1
Order By: Relevance
“…(19) However, there are factors other than age, such as sarcopenia and functional status, that likely play an additional role in determining prognosis. (20) We previously showed that hepatic encephalopathy independently impairs prognosis (21) ; however, more work needs to be done to determine the interaction between age, ACLF, and short-term and long-term outcomes. In addition, it would have been ideal to reevaluate patients for ACLF 3-5 days after diagnosis to determine if this better predicted mortality, as some have shown previously; however, these data were not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(19) However, there are factors other than age, such as sarcopenia and functional status, that likely play an additional role in determining prognosis. (20) We previously showed that hepatic encephalopathy independently impairs prognosis (21) ; however, more work needs to be done to determine the interaction between age, ACLF, and short-term and long-term outcomes. In addition, it would have been ideal to reevaluate patients for ACLF 3-5 days after diagnosis to determine if this better predicted mortality, as some have shown previously; however, these data were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age also negatively impacts survival in post‐surgery ACLF . However, there are factors other than age, such as sarcopenia and functional status, that likely play an additional role in determining prognosis . We previously showed that hepatic encephalopathy independently impairs prognosis; however, more work needs to be done to determine the interaction between age, ACLF, and short‐term and long‐term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…53 Frailty has consistently been shown to be a critical determinant of liver transplant outcomes, including hospitalizations, and mortality both before 2,52,54-57 and after liver transplantation. 53,[58][59][60][61] A range of tools to measure frailty and physical function have been studied in this population, and recent efforts to standardize frailty measurement in liver transplantation have yielded the Liver 2. Frailty measurements should be standardized and performed routinely in patients undergoing evaluation for liver transplantation.…”
Section: Frailty Considerations In Liver Transplantationmentioning
confidence: 99%
“…105,106 A Karnofsky performance status-based score has recently been proposed for the prediction of death after hospital discharge in cirrhosis. 107 The subgroup of patients with low MELD scores and high frailty may derive the greatest benefit from implementation of these measures. 102 However, functional tests evaluating frailty could be not enough discriminant in the homogeneous population of very high MELD patients.…”
Section: Therapiesmentioning
confidence: 99%